2019
DOI: 10.1038/s41393-018-0237-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer and internet use among people with long-standing spinal cord injury: a cross-sectional survey in the Netherlands

Abstract: Study design: Cross-sectional survey Objectives: To describe computer and Internet use (other than for work or study) among people with long-standing spinal cord injury (SCI), examine associations between demographic and lesion characteristics and Internet use, and examine associations between Internet use and mental health, participation, and life satisfaction. Setting: Community, The Netherlands Methods: Participants were 265 individuals living with SCI for at least 10 years, who were 18-35 at the onset of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…All participants had internet access, and this did not present as a barrier. This is consistent with other work showing people with spinal cord injury regularly access the internet [19,20] and embedding rehabilitation into this established context would not create additional hardships.…”
Section: Discussionsupporting
confidence: 90%
“…All participants had internet access, and this did not present as a barrier. This is consistent with other work showing people with spinal cord injury regularly access the internet [19,20] and embedding rehabilitation into this established context would not create additional hardships.…”
Section: Discussionsupporting
confidence: 90%
“…While our participants were relatively well-educated and financially secure, and, may, hence, have better availability of online resources than do less well educated and wealthy individuals with SCI [33,34], the literature documents that people with SCI are concerned about the validity and specificity of internet-derived information [14,17]. Consistent with these findings, while our participants were relatively reliant on the internet, over half of them worried that the materials they find there may not be accurate.…”
Section: Discussionsupporting
confidence: 66%
“…These findings are consistent with Florio et al [7], who found that manual wheelchairs were primarily used by persons with complete paraplegia, and walking aids such as crutches, walking frames, and leg braces were mainly used by those with an incomplete lesion. Additionally, we found that persons with complete tetraplegia considered the computer as the most important AD, reflecting the importance of advanced technology and the wide range of electronic devices that assist persons with tetraplegia, such as eye-tracking [25], an adapted keyboard, speech-recognition software [26], and screen readers [27]. In their survey involving 15 veterans with SCI, Collinger et al [4] found that the most important design characteristic for new technologies such as brain-computer interfaces was the capability for independent operation, closely followed by non-invasiveness.…”
Section: Discussionmentioning
confidence: 99%